2017
DOI: 10.1016/j.ghir.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Gender has to be taken into account in diagnosing adult growth hormone deficiency by the GHRH plus arginine test

Abstract: The GH response to stimulation by GHRH+ARG is gender-dependent, being lower in healthy males than in females. Gender should be considered when defining cut-off limits for peak GH concentrations in the GHRH+ARG test. The presently used BMI-related cut-off levels will lead to a significant misclassification of males as GH deficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Current pediatric guidelines do not mention sex in the interpretation of GH stimulation test results of children referred for short stature [3,4]. Moreover, recently published studies in children with short stature do not report sex differences in results of GH stimulation tests [93], although sex differences have been reported in adults undergoing GHRH þ arginine tests [94]. Given that the weighted mean age of participants was 10.2 years, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Current pediatric guidelines do not mention sex in the interpretation of GH stimulation test results of children referred for short stature [3,4]. Moreover, recently published studies in children with short stature do not report sex differences in results of GH stimulation tests [93], although sex differences have been reported in adults undergoing GHRH þ arginine tests [94]. Given that the weighted mean age of participants was 10.2 years, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to healthy men and women, IGF1 levels in GH-deficient adults are lower in women than in men ( 124 ). When healthy adults underwent GHRH plus arginine and arginine tests, several investigators found that peak GH levels are higher in females than males within the same BMI category ( 125 , 126 ). Thus, if sex differences are not taken into account, then males are at greater risk of being overdiagnosed with GHD.…”
Section: Individual Patient Considerationsmentioning
confidence: 99%
“…Furthermore, oral estrogen administration increases integrated GH concentration both in healthy pre-and postmenopausal women by virtue of lesser negative feedback due to lowered hepatic IGF1 generation (123). In contrast to healthy men and women, IGF1 levels in GH-deficient adults are lower in women than in men (124). When healthy adults underwent GHRH plus arginine and arginine tests, several investigators found that peak GH levels are higher in females than males within the same BMI category (125,126).…”
Section: Agementioning
confidence: 99%
“…These results indicated that stimulated GH studies allowed simulation of the dosage, as well as the therapeutic effects against acromegaly, based on early research and development stages. Our study was conducted exclusively for males in all species tested since the GH response to stimulation by GHRH + arginine is sex-dependent (Markkanen et al, 2017). Our studies reflected the E-R relationship of male and female patients with acromegaly, but an important limitation is the limited background of subjects in our studies.…”
Section: Discussionmentioning
confidence: 99%